1956
DOI: 10.3181/00379727-91-22359
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of Mitochondria in Irreversible Hemorrhagic Shock, I.

Abstract: Some studies were made of the influence of dietary molybdenum on intestinal alkaline phosphatase activity. It was observed that after one week on the experimental regimen 5 rats receiving 1200 p.p.m. molybdenum had significantly less (P< 0.01) intestinal phosphatase activity than 5 controls. Control and toxic values were 16.58 t 1.64 and 4.46 t 0.73 pM phosphate released/30'/mg protein respectively. Because of this rapid and pronounced effect, the influence of sodium molybdate on the intestinal phosphatase ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1958
1958
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
5
0
Order By: Relevance
“…The signs of damaged glycid metabolism include Ihe lowering of gly cogen reserves in the liver and muscles (6, 8, i), 10), the heightening of the blood sugar level with a gradual lowering afterwards (4,15,17), the higher level of lactic and pyruvic acid in the blood (1,4,5,14,22) and the lower glycolytic activity of the blood (20).Factors which cause these changes are not exactly defined. Therefore we estimated in this work changes in the utilization of glucose by the red blood cells and tried to find out Ihe cause of these changes.…”
mentioning
confidence: 99%
“…The signs of damaged glycid metabolism include Ihe lowering of gly cogen reserves in the liver and muscles (6, 8, i), 10), the heightening of the blood sugar level with a gradual lowering afterwards (4,15,17), the higher level of lactic and pyruvic acid in the blood (1,4,5,14,22) and the lower glycolytic activity of the blood (20).Factors which cause these changes are not exactly defined. Therefore we estimated in this work changes in the utilization of glucose by the red blood cells and tried to find out Ihe cause of these changes.…”
mentioning
confidence: 99%
“…A preliminary report by Panagos, Beyer, and Masoro (1958) has shown that liver mitochondria are stress points in animals exposed to cold, and explain the resulting uncoupling of oxidative phosphorylation by intermediate action of increased thyroid secretion. The studies of cardiac mitochondria by Strawitz and Hift (1956) and by Hift and Strawitz (1958) with animals in irreversible haemorrhagic shock have demonstrated profound morphological, metabolic, and chemical alterations. Mediation by hormonal stress, including thyroid excess, is likely.…”
Section: Hormonal Controlmentioning
confidence: 99%
“…Moreover, mitochondria are also important in apoptosis via a number of mitochondrial proteins (76). With reduced oxygen availability, such as that occurring during severe hemorrhage, mitochondrial function is compromised as indicated by decreased ATP generation, impaired electron transport, and increased production of reactive oxygen species (ROS) (19,25,112,121).…”
Section: Previous Investigations In Humansmentioning
confidence: 99%
“…Moreover, mitochondria are also important in apoptosis via a number of mitochondrial proteins (76). With reduced oxygen availability, such as that occurring during severe hemorrhage, mitochondrial function is compromised as indicated by decreased ATP generation, impaired electron transport, and increased production of reactive oxygen species (ROS) (19,25,112,121).Mitochondrial DNA codes for 13 mitochondrial proteins (MP) (3), and nuclear DNA is responsible for the additional MP that not only vary in number among species (44,99,117), but also among tissues within species (44). Such MP may be divided into categories of known function that include: 1) oxidative phosphorylation-associated proteins; 2) signaling proteins; 3) transporter and channel-associated proteins; 4) RNA, DNA, and protein synthesis-related proteins; 5) metabolic proteins; 6) cell death and defense proteins; 7) redox proteins; 8) proteases and protein…”
mentioning
confidence: 99%